Peran kualitas dan ketersediaan alat dalam praktikum biologi dan implikasinya terhadap pembelajaran di sekolah menengah atas - Halim, Helena; Azzahra, Nasywa; Azzahrianto, Octavia Putri; Zahra, Raudahtul (Papanda Journal of Mathematics and Science Research, 2025)
Practicum is one of the important components in learning biology in Senior High School (SMA). The success of practicum is influenced by the availability of adequate practicum tools and materials, as well as the quality of these tools. This study aims to analyze the role of quality and availability of biology practicum tools and their implications for learning in high school. The research method used was a survey with data collection techniques through questionnaires and observations. The samples of this study were biology teachers and high school students in certain areas. The results showed that the quality and availability of adequate biology lab equipment play an important role in supporting biology learning in high school. Practical tools that are of good quality and adequately available can improve concept understanding, science process skills, and student learning motivation. The implication is the need for increased budget and attention from the school and government related to the provision of quality biology lab equipment and sufficient learning needs in high school